2012
DOI: 10.1080/08870446.2011.578745
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic growth after childbirth: A prospective study

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Permanent repository link

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 56 publications
(60 reference statements)
8
47
2
Order By: Relevance
“…Leung et al (2010) identifi ed signifi cant association between greater social support and posttraumatic growth (28). In a study investigating posttraumatic growth following childbirth, Sawyer et al (2012) found no association between PTG and social support (29). Similarly, no statistically signifi cant association was found in another study investigating coping strategies, social support, attachment styles and posttraumatic growth in cancer survivors (14).…”
Section: Discussionmentioning
confidence: 98%
“…Leung et al (2010) identifi ed signifi cant association between greater social support and posttraumatic growth (28). In a study investigating posttraumatic growth following childbirth, Sawyer et al (2012) found no association between PTG and social support (29). Similarly, no statistically signifi cant association was found in another study investigating coping strategies, social support, attachment styles and posttraumatic growth in cancer survivors (14).…”
Section: Discussionmentioning
confidence: 98%
“…Finally, as in other studies of international versions of the PTGI (Jaarsma et al, 2006), we did not assess the perceived impact of divorce experience in our sample. This methodological option is based on the recent conceptual views of psychological growth, in which stressrelated growth measures can be administered to assess individual's perception of personal changes in the self, interpersonal relationships, and life philosophy in a wide diversity of life events (Krumrei et al, 2009;Sawyer & Ayers, 2009;Staudinger & Kunzmann, 2005;Taku et al, 2008;Tedeschi et al, 2007). On the other hand, the assessment of perceived negative impact of divorce could have been relevant since, according to Tedeschi and Calhoun (1996), the comparison of the PTGI scores between highly stressed individuals and nonhighly stressed individuals may be an additional tool to verify PTG construct validity, by predicting that highly stressed individuals would be more likely to report higher levels of PTG (Tedeschi & Calhoun, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Methodological quality of studies was graded using rating criteria based on those used in previous reviews of perinatal research (Sawyer et al, 2012;Andersen et al, 2012). This rated study aims/hypotheses, inclusion and exclusion criteria, data collection, PTSD measure, sample representativeness, response rate, and analysis of differences between participants and nonparticipants.…”
Section: 3data Extraction and Quality Assessmentmentioning
confidence: 99%